Continuous thermosalinograph oceanography along RV POLARSTERN cruise track PS134 - Mario Hoppmann; Sandra Tippenhauer; Karsten Gohl (PANGAEA, 2023)
Raw data acquired by two SBE21 thermosalinograph and two auxiliary SBE38 temperature sensor (Sea-Bird Scientific, USA) installed in an underway seawater flow-through system on board RV Polarstern were processed to yield a calibrated and validated data set of temperature and salinity along the cruise track. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) at a resolution of 1 sec, and converted to temperature and conductivity using the pre-deployment factory calibration coefficients. The converted data were averaged to 1 min values, outliers were removed, and sensor drift was corrected using coefficients obtained from a post-season calibration performed at Sea-Bird at the end of the measurement season. Salinity was calculated from internal temperature, conductivity and pressure according to the PSS-78 Practical Salinity Scale. Processed data are provided as 1 min means of seawater temperature, conductivity and salinity, aligned with position data taken from the master track. Quality flags are appended according to the SeaDataNet Data Quality Control Procedures (version from May 2010). More details are described in the attached processing report.